Effect of long-term rice straw incorporation on soil phosphorus availability in a sandy loam soil - KAUR, MANDEEP; SAINI, SAT PAL (Journal of Soil and Water Conservation, 2020)
A field experiment was conducted on a sandy loam soil at Ludhiana to investigate the effect of longterm rice straw incorporation (0-10 t ha-1 yr-1) and fertilizer N (0-150 kg N ha-1) application on soil phosphorus fractions. The treatments were arranged in a split plot design with three replications, with fertilizer N (N0, N90, N120 and N150) in main plots and rice straw (RS0, RS5, RS7.5 and RS10) in sub-plots. Rice straw incorporation (RS7.5) significantly (p<0.05) increased the concentration of inorganic P fractions viz. saloid-P, aluminium-P (Al-P), iron-P (Fe-P), reductant-P (Red-P), calcium-P (Ca-P), organic-P and total- P by 11.4, 11.0, 12.5, 18.5, 24.6, 14.9 and 20.3%, respectively compared with control (RS0) in the surface (0- 15 cm soil layer) soil. The concentration of saloid-P, Al-P, Fe-P and Red-P increased significantly by 0.5, 5.6, 1.3 and 1.1 mg kg-1, respectively with N150, compared with N0. The effect of increased N levels to N120 on saloid-P, Al-P, Fe-P and Ca-P concentration was statistically non-significant. However, Ca-P increased significantly in N120 treatment, compared with N0. Concentration of organic-P was not influenced by N application. Irrespective of the treatments, inorganic-P was dominating fraction as organic-P constituted 8% only of the total P content. Among different fractions, Ca-P was the most dominant (65% of total-P) and the content of soil inorganic P fractions followed the sequence saloid-P < Red-P <Fe-P < Al-P < Ca-P in a sandy loam soil after 7 years of rice-wheat cropping. Different P fractions exhibited a significant linear positive correlation with soil organic carbon (SOC) (r=0.848-0.958**, p<0.01), available-P (r=0.876- 0.968**, p<0.01).